ВПЛИВ ПЕДАГОГІЧНИХ КОМУНІКАЦІЙ НА ФОРМУВАННЯ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ ПЕДАГОГІВ (Педагогіка вищої та середньої школи, 2008)
The article reveals the main conceptual apparatus of the communication theory, the attention is paid to the means of communication which pédagogues use. The notions “communication” and “intercourse” are analysed comparatively, also the communicativemodels are considered.